Efficacy of Intercropping as a Management Tool for the Control on Insect Pests of Cabbage in Ghana 1H m 2m - Timbilla, JA. (Tropicultura, 2001)
The efficacy of intercropping cabbage with other vegetables and herbs as a management tool in migitating insect pests problems of cabbage was investigated in the field at Kwadaso, Kumasi during a three season period in the forest region of Ghana. The results showed that Plutella xylostella could be effectively controlled when cabbage is intercropped with onion, spearmint and tomato. However, there is the need to control Hellula undalis in endemie areas with pesticides up to six weeks after transplanting. Both Karate (cyhalothrin) and Dipel 2X (the biopesticide Bacillus thuringiensis subsp. Kurstaki) were effective in mitigating the problem of H. undalis in the intercropping experiments and both are recommended.